PENGARUH PROXY LEVERAGE TERHADAP NILAI PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR PADA BEI TAHUN 2016-2020 - Arijo Isnoer Narjono; Titis Sri Murni; Mokhammad Hariyadi Eko Romadon; Ning Mukti Indriyani (CV. Denasya Smart Publisher, 2024)
The purpose of this research is to analyze the effect of leverage on firm value. Independent variables used are Leverage proxies, namely Debt to Equity Ratio (DER) dan Debt to Asset Ratio (DAR). The Dependent variable used is a proxy for firm value, namely Price To Book Value (PBV). The population in this study are chemical companies sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling method used was purposive sampling method with a sample of 8 chemical companies during the observation period of 5 consecutive years so that the total sample was 40. The analytical method of this study uses multiple linear regression. The results of this study indicate that (1) Debt To Equity Ratio (DER) has a negative and significant effect on Price to Book Value (PBV). This is known from the test results where the calculated T value = -4.535 is less than T table = 1.685 and the significant value of the Debt to Equity Ratio (DER) variable is 0.000 which is less than 0.05. (2) Debt To Asset Ratio (DAR) has a positive and significant effect on Price to Book Value (PBV). It is known from the test results where t count = 4.560 is greater than t table = 1.685 and the significant value of the Debt to Asset Ratio (DAR) variable is 0.000 less than 0.05. Meanwhile, the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) simultaneously have a significant positive effect on the Price To Book Value (PBV) of chemical companies listed on the Indonesia Stock Exchange (IDX) in the period 2016-2020. It is known from the calculated F value of 10.524 and the F table value of 3.19 so that the calculated F value > F table value, namely 10.524 > 3.19 with a significance value of 0.000 <0.05.